2019
DOI: 10.1016/j.ijppaw.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Translocation a potential corridor for equine piroplasms in Cape mountain zebra (Equus zebra zebra)

Abstract: Translocation of animals in fragmented habitats is an important means of dispersal and gene flow, however, the movement of animals has led to the spread of various diseases globally and wildlife are often the reservoirs of these diseases. Currently, Cape mountain zebra are translocated within South Africa as a management method for augmentation of isolated and fragmented populations. The movement of pathogens due to translocations in local regions have gone largely unchecked, particularly where there may still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition to horses, both parasites have been reported in other equids including domestic donkeys [109,137,138,181,[212][213][214][215][216][217][218][219], wild donkeys [214,220], mules [109,138,181,212,216], and zebras [102,214,[220][221][222][223][224][225]; and in non-equids, including dogs [145,[226][227][228][229][230], camels [231,232], cattle [233], and a tapir [234] (recently reviewed in: [5,214]). Donkeys are considered more resistant to infection than horses [217]; however, this assumption is not well established, since the data regarding domestic equids (donkeys and mules) is less comprehensive than in horses, and many surveys use a population of different equine species.…”
Section: A Review Of Ep Epidemiology In the Last 20 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to horses, both parasites have been reported in other equids including domestic donkeys [109,137,138,181,[212][213][214][215][216][217][218][219], wild donkeys [214,220], mules [109,138,181,212,216], and zebras [102,214,[220][221][222][223][224][225]; and in non-equids, including dogs [145,[226][227][228][229][230], camels [231,232], cattle [233], and a tapir [234] (recently reviewed in: [5,214]). Donkeys are considered more resistant to infection than horses [217]; however, this assumption is not well established, since the data regarding domestic equids (donkeys and mules) is less comprehensive than in horses, and many surveys use a population of different equine species.…”
Section: A Review Of Ep Epidemiology In the Last 20 Yearsmentioning
confidence: 99%
“…The differences in the distribution of each genotype is important in understanding the spread of parasites and the infection dynamics within and between equine populations. Recent studies showed that in endemic areas, many horses are co-infected with several genotypes of T. equi, and that the predominant genotype or genotypes differ between equine hosts and subpopulations [102,125,221,255]. Co-infection is also possible with other related species, including T. haneyi [28] and B. caballi (Table 1).…”
Section: Theileria Equi 18s Rrna Genotypes and Their Global Distributionmentioning
confidence: 99%
“…The prevalence of piroplasm in Kenyan elephants at 13.5% was lower compared with infection patterns in other large African wild hosts. For example, the prevalence of piroplasm has been recorded to be 100% in common zebra, Equus quagga , Cape zebra, Equus zebra and Grevy’s zebra, Equus grevyi [30, 42, 43], 100% in free ranging spotted hyenas, Crocuta crocuta [44] and 92–100% in the African buffalo, Syncerus caffer [45]. However, the prevalence of piroplasm was comparable to that in south African black rhino, Diceros bicornis at 18.6% [46].…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious and widely studied negative consequence of translocation on antelopes is hybridization (Dalton et al, 2014;Grobler et al, 2018;van Wyk et al, 2019). Translocation can also facilitate spread of disease and even introduce novel diseases to naive habitats (Glover et al, 2020;Lloyd, 2000;Smith et al, 2019). In antelopes, pathogen transmission from introduced wildlife may devastate adjacent livestock, and the reverse is also true (Glover et al, 2020).…”
Section: Translocationmentioning
confidence: 99%